Implementasi Kelas Ibu Hamil (Penyuluhan Perawatan Payudara Masa Kehamilan dan Menyusui di Puskesmas I Denpasar Utara) - Ni Made Ari Febriyanti; Ni Ketut Ayu Sugiartini (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This community service aims to provide education to pregnant women in the second and third trimesters about the benefits of breast care during pregnancy and breastfeeding. The method used in this service is to provide online counseling about breast care during pregnancy and breastfeeding during class for pregnant women. Participants in this service program are pregnant women in the second and third trimesters who take part in the pregnant women class program at Puskesmas I, North Denpasar. After being given counseling, there was an increase in knowledge of pregnant women about breast care during pregnancy and breastfeeding.